2014
DOI: 10.1016/j.tsf.2013.10.135
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth and electronic structure of a layered zinc pnictide semiconductor, β-BaZn2As2

Abstract: BaZn2As2 is expected for a good p-type semiconductor and has two crystalline phases of an orthorhombic α phase and a higher-symmetry tetragonal β phase. Here, we report high-quality epitaxial films of the tetragonal β-BaZn2As2 were grown on single-crystal MgO (001) substrates by a reactive solid-phase epitaxy technique. Out-of-plane and in-plane epitaxial relationships between the film and the substrate were BaZn2As2 (00l )//MgO (001) and BaZn2As2 [200]//MgO [200], respectively. The full-widths at half maximum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…1 a, we show polycrystalline X-ray diffraction patterns of Sr-doped (Ba Sr )(Zn Co ) As ( x = 0.05, 0.10 and 0.15) and Sb-doped Ba(Zn Co ) (As Sb ) ( x = 0.05 and 0.10). We should mention that BaZn As exhibit two different crystal structures, the low-temperature orthorhombic phase -BaZn As (space group Pnma) 29 and the high-temperature tetragonal phase -BaZn As (space group I4/mmm) as a semiconductor with a bandgap 0.2 eV 30 , 31 . Both p -type DMS (Ba,K)(Zn,Mn) As and n -type DMS Ba(Zn,Co) As were achieved in the high temperature tetragonal phase 17 , 28 .…”
Section: Resultsmentioning
confidence: 99%
“…1 a, we show polycrystalline X-ray diffraction patterns of Sr-doped (Ba Sr )(Zn Co ) As ( x = 0.05, 0.10 and 0.15) and Sb-doped Ba(Zn Co ) (As Sb ) ( x = 0.05 and 0.10). We should mention that BaZn As exhibit two different crystal structures, the low-temperature orthorhombic phase -BaZn As (space group Pnma) 29 and the high-temperature tetragonal phase -BaZn As (space group I4/mmm) as a semiconductor with a bandgap 0.2 eV 30 , 31 . Both p -type DMS (Ba,K)(Zn,Mn) As and n -type DMS Ba(Zn,Co) As were achieved in the high temperature tetragonal phase 17 , 28 .…”
Section: Resultsmentioning
confidence: 99%
“…2(b) as an example. The values of energy gap E g are between 0.031 and 0.048 eV, which are about an order of magnitude smaller than that of the parent compound BaZn 2 As 2 25. We have conducted Hall effect measurement on Ba(Zn 0.75 Mn 0.125 Cu 0.125 ) 2 As 2 , but the large resistivity prevents us to accurately determine the carrier density.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the T C of (Ba, K)(Zn, Mn) 2 As 2 single crystal has been reported to reach 230 K24. (Ba, K)(Zn, Mn) 2 As 2 was synthesized by doping Mn and K into the parent compound β -BaZn 2 As 2 which is a direct gap (0.2 eV) semiconductor25, where the substitution of Mn for Zn and K for Ba introduces spins and hole carriers, respectively.…”
mentioning
confidence: 99%
“…Recently, first-principles calculations for the -and -BaZn2As2 phases reported that they have complicated and highlyanisotropic electronic structures due to the unusual cation-anion and anion-anion hybridizations; 28 however, it does not provide an explanation for the extreme narrow bandgap of -BaZn2As2. Further, the previously-reported bandgap value 25 is not so reliable due to the interference of the substrate optical absorption, and no other experimental data on its electronic structure has been provided.…”
Section: Introductionmentioning
confidence: 94%